2002
DOI: 10.3758/bf03196316
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological dissociation of retrieval orientation and retrieval effort

Abstract: The neural correlates of retrieval orientation-the differential processing of retrieval cues according to the form of the sought-for information-and retrieval effort were investigated in a factorial design. ERPs elicited by test words were recorded during four recognition memory tests. Orientation was manipulated by varying study material: The study phases preceding two of the tests employed pictures, whereas the study phases preceding the other two tests employed words. Effort was manipulated by varying diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
87
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 25 publications
15
87
3
Order By: Relevance
“…First, the failure to recollect nontarget items could have arisen because of cue bias (Anderson & Bjork, 1994). According to this possibility, the subjects adopted a retrieval orientation (Robb & Rugg, 2002;Rugg & Wilding, 2000) that, while optimizing the processing of test items as cues for the recollection of target information, made these items ineffectual as cues for nontarget recollection.…”
Section: Discussionmentioning
confidence: 99%
“…First, the failure to recollect nontarget items could have arisen because of cue bias (Anderson & Bjork, 1994). According to this possibility, the subjects adopted a retrieval orientation (Robb & Rugg, 2002;Rugg & Wilding, 2000) that, while optimizing the processing of test items as cues for the recollection of target information, made these items ineffectual as cues for nontarget recollection.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, comparing memory for pictures versus words has been used as a tool in memory research. Such studies have helped to better understand aspects of memory including false recognition (Israel & Schacter, 1997), the distinctiveness heuristic (Budson et al, 2005b), and retrieval orientation (Robb & Rugg, 2002). Examining memory for pictures and words has also helped us to better understand memory impaired populations (Budson et al, 2002a;Budson et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Deep versus shallow processings in the study phase have been found to engender diVerent ERP patterns during retrieval processing (Rugg, Allan, & Birch, 2000). Robb and Rugg (2002) had participants study lists of pictures or words, in diVerent blocks, and used words as recognition cues for both. The processing of new words diVered markedly depending on whether it occurred in the context of studied words or studied pictures.…”
Section: Retrieval Orientationsmentioning
confidence: 99%